2022
DOI: 10.1021/acs.jafc.2c00981
|View full text |Cite|
|
Sign up to set email alerts
|

New Water-Soluble Cytokinin Derivatives and Their Beneficial Impact on Barley Yield and Photosynthesis

Abstract: Solubility of growth regulators is essential for their use in agriculture. Four new cytokinin salts6-benzylaminopurine mesylate (1), 6-(2-hydroxybenzylamino)purine mesylate (2), 6-(3-hydroxybenzylamino)purine mesylate (3), and 6-(3methoxybenzylamino)purine mesylate (4)were synthesized, and their crystal structures were determined to clarify structural influence on water solubility. The mesylates were several orders of magnitude more water-soluble than the parent CKs. The new salts significantly reduced chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…These characteristics resembled those found in other Euphorbiaceae species and similarities in protein structure with species from the Euphorbiaceae family and Arabidopsis. The results of multiple comparisons showed that the RR17 proteins in Euphorbiaceae demonstrated the presence of the typical structural domain REC A-type ARR, a downstream response factor of cytokinin in Arabidopsis, and a key node in the regulation of CK signaling [6,23], and functions as a positive regulator of CK signaling [24]. However, studies in Populus tremula indicated that the downstream response factor ARR17, responsible for sexual differentiation in poplar, did not rely on CK action.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics resembled those found in other Euphorbiaceae species and similarities in protein structure with species from the Euphorbiaceae family and Arabidopsis. The results of multiple comparisons showed that the RR17 proteins in Euphorbiaceae demonstrated the presence of the typical structural domain REC A-type ARR, a downstream response factor of cytokinin in Arabidopsis, and a key node in the regulation of CK signaling [6,23], and functions as a positive regulator of CK signaling [24]. However, studies in Populus tremula indicated that the downstream response factor ARR17, responsible for sexual differentiation in poplar, did not rely on CK action.…”
Section: Discussionmentioning
confidence: 99%